2008
DOI: 10.3174/ajnr.a1229
|View full text |Cite
|
Sign up to set email alerts
|

Which CT Perfusion Parameter Best Reflects Cerebrovascular Reserve?: Correlation of Acetazolamide-Challenged CT Perfusion with Single-Photon Emission CT in Moyamoya Patients

Abstract: BACKGROUND AND PURPOSE: CT perfusion (CTP) is a more readily accessible method for evaluation of cerebral perfusion than single-photon emission CT (SPECT). We assessed whether there is any resting or drug-challenged CTP parameter correlating with cerebrovascular reserve (CVR) obtained by SPECT in Moyamoya patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…93 Another study correlated ACZchallenged PCT with SPECT in patients with Moyamoya disease and showed that baseline PCT parameters, including CBV and MTT, correlated weakly with the CVR obtained with SPECT. 33 The study demonstrated that percentage change of CBF correlated well with quantitative SPECT CVR measurements.…”
Section: Moyamoya Diseasementioning
confidence: 68%
See 1 more Smart Citation
“…93 Another study correlated ACZchallenged PCT with SPECT in patients with Moyamoya disease and showed that baseline PCT parameters, including CBV and MTT, correlated weakly with the CVR obtained with SPECT. 33 The study demonstrated that percentage change of CBF correlated well with quantitative SPECT CVR measurements.…”
Section: Moyamoya Diseasementioning
confidence: 68%
“…The feasibility of CTP in the evaluation of chronic ischemia has been encouraging in various studies. [32][33][34] Furukawa et al 35 studied the usefulness of PCT in the evaluation of chronic cerebral ischemia and compared the technique with Xe-CT. In their study, the relative scores of CBF obtained by PCT correlated well with Xe-CT values, though the absolute values did not show as good a correlation.…”
Section: Pctmentioning
confidence: 99%
“…16,17 Longer MTT indicated pre-existing hemodynamic impairment and predisposed the patient to HPS. 18,19 The high signal intensity of subcortical white matter on FLAIR imaging represented edematous change and implied impaired dysautoregulation, likely potentiated by the venous stasis. If one reviewed the 3 patients with abnormal MR imaging findings, no incidences of contralateral stenosis or poor collaterals were seen, their mean age was 70 years, and strict postoperation blood pressure control was also performed.…”
Section: Discussionmentioning
confidence: 99%
“…11 Quantitative assessment of CVR by using the acetazolamide challenge is an additional measurement of hemodynamic impairment in patients with major cerebral artery occlusive disease. 12 The risk of developing an ischemic event is known to be higher in patients with reduced CVR. 13,14 The CVR, therefore, often aids in decision-making for treatment options and is used to follow the course of the disease.…”
Section: Discussionmentioning
confidence: 99%